The outcome of implementing antimicrobial stewardship program for hospitalized children - El-Nawawy, Ahmed A.; Wagdy, Reham M.; Abou Ahmed, Ahmed Kh.; Moustafa, Marwa A. (International Journal Of Community Medicine And Public Health, 2018)
Background: An effective approach to improve antimicrobial use for hospitalized patients is an antimicrobial stewardship program (ASP). The present study aimed to implement ASP for inpatient children based on prospective-audit-with-feedback intervention in order to evaluate the impact on patient’s outcome, antimicrobial use, and the hospital cost. Methods: The study was conducted throughout 6 months over 275 children admitted with different infections at Main Children’s hospital in Alexandria included; group I (with ASP) and group II (standard antimicrobials as controls). Results: The study revealed that on patient’s admission, single antibiotic use was higher among the ASP group while double antimicrobial therapy was higher among the non-ASP with significant difference (p=0.001). Less percentage of patients who consumed vancomycin, meropenem amoxicillin-clavulanic and metronidazole was observed among ASP group with a significant difference of the last two drugs when compared to controls (p=<0.001, 0.011, respectively). The study reported the higher percent of improved ASP patient’s after 72 hours of admission with a significant difference to controls (73.2% versus 62.5%, p=0.038). Complications occurred more likely for the non-ASP group (odds ratio 7.374 with 95% CI 1.68-32.33). In general, there was a clear reduction of the patient antibiotic cost/day and overall cost per patient, however, it was not significant among the studied patients. Conclusions: Our local ASP model provided a high quality of care for hospitalized children and effectively reduced the antimicrobial consumption.